A nomenclature for fossil and living turtles using phylogenetically defined clade names - Joyce, Walter G. (2021)
Over the last 25 years, researchers, mostly paleontologists, have developed a system of rank-free, phylogenetically defned names for the primary clades of turtles. As these names are not considered established by the PhyloCode, the newly created nomenclatural system that governs the naming of clades, we take the opportunity to convert the vast majority of previously defned clade names for extinct and extant turtles into this new nomenclatural framework. Some previously defned names are converted with minor adjustments. We also defne a number of new clade names to close apparent nomenclatural gaps. In total, we establish 113 clade names, of which 79 had already received phylo‑ genetic defnitions and 34 are new.